Clinical and Laboratory Features of Acute Porphyria: A Study of 36 Subjects in a Chinese Tertiary Referral Center. (29th November 2016) - Yang, Jing; Chen, Qianlong; Yang, Hang; Hua, Baolai; Zhu, Tienan; Zhao, Yongqiang; Zhu, Huadong; Yu, Xuezhong; Zhang, Li; Zhou, Zhou
Abstract : Porphyria is a group of eight metabolic disorders characterized by defects in heme biosynthesis. The presentation of porphyria is highly variable, and the symptoms are nonspecific, which accounts in part for delays in establishing a diagnosis. In this study, we report the characteristics of 36 Chinese acute porphyria patients. Most of them were female (33/36), and the median age was 25.3 years (range 18–45 years). The most frequent presenting symptom was abdominal pain (32/36). Hyponatremia was the most common electrolyte abnormality (29/36), and the serum sodium concentration was significantly negatively correlated with convulsion (p = 0.00 ). Genetic testing provided a precise diagnosis of the patients. Genetic analysis of the porphobilinogen deaminase ( PBGD ) gene was performed for 10 subjects. Of them, 9 were found to harbor a mutation in the PBGD gene, proving a diagnosis of acute intermittent porphyria, and, in 1 case, a novel Cys209Term mutation was found.